EFFECTS OF TRAUMA, HEMORRHAGE AND RESUSCITATION IN AGED RATS - Hawkins, Bridget E. (2012)
Traumatic brain injury (TBI) is a leading cause of death in the elderly and the incidence of mortality and morbidity increases with age. This study tested the hypothesis that, after TBI followed by hemorrhagic hypotension (HH) and resuscitation, cerebral blood flow (CBF) would decrease more in aged compared with young rats. Young adult (4–6 months) and aged (20–24 months) male Sprague-Dawley rats were anesthetized with isoflurane, prepared for parasagittal fluid percussion injury (FPI) and randomly assigned to receive either moderate FPI (2.0 atm) only, moderate FPI + severe HH (40 mm Hg for 45 minutes) followed by return of shed blood, or sham FPI. Intracranial pressure (ICP), CBF, and mean arterial pressure (MAP) were measured and, after twenty-four hours survival, the rats were euthanized and their brains were sectioned and stained with Fluoro-Jade (FJ), a dye that stains injured neurons. After moderate FPI, severe HH and reinfusion of shed blood, MAP and CBF were significantly reduced in the aged group, compared to the young group. Both FPI and FPI + HH groups significantly increased the numbers of FJ-positive neurons in hippocampal cell layers CA1, CA2 and CA3 (p < 0.05 vs Sham) in young and aged rats. Despite differences in post-resuscitation MAP and CBF, there were no differences in the numbers of FJ-positive neurons in aged compared to young rats after FPI, HH and blood resuscitation. Although cerebral hypoperfusion in the aged rats was not associated with increased hippocampal cell injury, the trauma-induced reductions in CBF and post resuscitation blood pressure may have resulted in damage to brain regions that were not examined or neurological or behavioral impairments that were not assessed in this study. Therefore, the maintenance of normal blood pressure and cerebral perfusion would be advisable in the treatment of elderly patients after TBI.